Enhancement of the Adsorption of Co(II) and Ni(II) Ions onto Peanut Hulls through Esterification Using Citric Acid - A. Hashem; E.S. Abdel-Halim; Kh.F. El-Tahlawy; A. Hebeish (Adsorption Science & Technology)
Peanut hulls were modified chemically by esterification with citric acid under conditions which yielded hulls rich in carboxyl content. The esterified products thus obtained were used in the removal of Co(II) and Ni(II) ions from aqueous solutions. The factors affecting the esterification reaction and the adsorption of the metal cations onto the peanut hulls before and after esterification were thoroughly investigated. The results obtained highlighted the following conclusions. The optimum conditions for esterification involve the treatment of peanut hulls (1 g) with 12.4 mmol citric acid in the presence of a very small amount of water for 2 h at 140°C. Similarly, the optimum pH for the adsorption of cobalt(II) ions onto the peanut hulls citrate was 7.0. The adsorption capacity, q e (mg/g), of Co(II) ions onto the peanut hulls citrate increased on increasing the extent of esterification, expressed as mequiv. —COOH/100 g sample. The maximum values for the adsorption capacity, q max , were 28.7 mg/g and 270.3 mg/g on native and peanut hulls citrate, respectively. The q max values for of Ni(II) ion adsorption were 5 mg/g and 175.4 mg/g on native and peanut hulls citrate, respectively. The equilibrium data were well fitted by the Langmuir and Freundlich adsorption models and showed the large capacity of peanut hulls citrate in the removal of Co(II) and Ni(II) ions from aqueous solutions.